The Multiple “I” Within the Narrative of William Faulkner’s Absalom! Absalom! - Anjarsari, Fitrilya (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
This research aims to understand the connectivity between a writer’s psyche and the act of narrative creation within a novel. A literary work or novel that is chosen to be the material object in this research is a work from William Faulkner entitled Absalom, Absalom! This novel has a complicated narrative style in which the storyline is not linear; moreover, some too many narrators appear to replace the main character. The theory of schizoanalysis will be applied to get the result that the novel has a schizophrenia tendency in its narrative style. The word schizophrenia as it is explained by Deleuze and Guattari is a form of a breakthrough. By examining the narrative style it is concluded that the novel had schizophrenic tendencies and Faulkner has offered his readers new ways to free themselves from the binary opposition caused by the grand narrative in history.